Identification of laminin α5 short arm peptides active for endothelial cell attachment and tube formation. (21st February 2017) - Kikkawa, Yamato; Sugawara, Yumika; Harashima, Nozomi; Fujii, Shogo; Ikari, Kazuki; Kumai, Jun; Katagiri, Fumihiko; Hozumi, Kentaro; Nomizu, Motoyoshi
Abstract : Laminin‐511, a major component of endothelial basement membrane, consists of α 5, β 1, and γ 1 chains. The short arm region of the α 5 chain is a structural feature of endothelial laminins. In this study, we identified active sequences for human umbilical vein endothelial cells (HUVECs) using recombinant proteins and synthetic peptides. The short arm of the α 5 chain contains three globular domains [laminin N‐terminal globular domain, laminin 4 domain a, and laminin 4 domain b (LN, L4a, and L4b)] and three rod‐like elements [laminin epidermal growth factor‐like domain a, b, and c (LEa, LEb, and LEc)]. The cell attachment assay using recombinant proteins showed that RGD‐independent cell attachment sites were localized in the α 5LN‐LEa domain. Further, we synthesized 70 peptides covering the amino acid sequences of the α 5LN‐LEa domain. Of the 70 peptides, A5‐16 (mouse laminin α 5 230–243: LENGEIVVSLVNGR) potently exhibited endothelial cell attachment activity. An active sequence analysis using N‐terminally and C‐terminally truncated A5‐16 peptides showed that the nine‐amino acid sequence IVVSLVNGR was critical for the endothelial cell attachment activity. Cell adhesion to the peptides was dependent on both cations and heparan sulfate. Further, the A5‐16 peptide inhibited the capillary‐like tube formation of HUVECs with the cells forming small clumps with short tubes. The eight‐amino acid sequence EIVVSLVN in the A5‐16 peptide was critical to inhibit HUVEC tube formation. This amino acid sequence could be useful for grafts and thus modulate endothelial cell behavior for vascular surgery. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The short‐arm region of the α5 chain in laminin‐511 (LM‐511) is a structural feature of endothelial laminins. A5‐16 peptide derived from LN domain potently exhibits endothelial potently cell attachment activity and inhibits the capillary‐like tube formation of human umbilical endothelial cells (HUVECs). The amino acid sequence of A5‐16 peptide would be useful for the design of vascular biomaterials.